Gambaran Karakteristik Pasien Hipertensi di Puskesmas Gunung Jati Cirebon - Alika Sabrina Jamil; Thysa Thysmelia Affandi; Sherly Cancerita (Universitas Malahayati Lampung, 2026)
ABSTRACT The prevalence of hypertension according to Riskesdas in 2018, West Java is ranked second, namely around 39.6% of its population has hypertension while Cirebon Regency according to the West Java Health Profile in 2022 is ranked 17th out of 27 cities or regencies whose hypertension patients reached 4.46% of around 2,217 thousand residents and based on the Cirebon Regency Health Profile in 2021. Data from the Gunung Jati Health Center, hypertension is ranked fifth, around 8.2% of the most common diseases in 2023, totaling 1994 people. To determine the characteristics of age, gender, education, socioeconomic status, smoking habits, coffee consumption, adherence to a low-salt diet and physical activity of hypertension patients at the Gunung Jati Health Center, Cirebon. This study uses descriptive observational, which was conducted at the Gunung Jati Health Center in May-June 2025. The sample size is 95 respondents. With total sampling through primary data, namely by questionnaire. Data analysis used univariate analysis. The results using univariate analysis included age (49,2%), gender (83,1%), education (58,5%), socioeconomic status (96,9%), smoking habits (90,8%), coffee consumption (33,8%), adherence to a low-salt diet (93,8%), and physical activity (69,2%). This study describes the characteristics of age, gender, education, socioeconomic status, smoking habits, coffee consumption, adherence to a low-salt diet, and physical activity in hypertensive patients. Keywords: Hypertension, Adherence to A Low-Salt Diet, Physical Activity. ABSTRAK Prevalensi hipertensi menurut Riskesdas pada tahun 2018, Jawa Barat menjadi urutan kedua yaitu sekitar 39,6% penduduknya mengalami hipertensi sedangkan Kabupaten Cirebon menurut Profil Kesehatan Jawa Barat pada tahun 2022 menjadi urutan ke-17 dari 27 Kota atau Kabupaten yang pasien hipertensinya mencapai 4,46% dari sekitar 2.217 ribu penduduk dan berdasarkan Profil Kesehatan Kabupaten Cirebon tahun 2021. Data dari Puskesmas Gunung Jati penyakit hipertensi menduduki peringkat kelima sekitar 8,2% penyakit terbanyak pada tahun 2023 yang berjumlah 1994 orang. Untuk mengetahui gambaran karakteristik dari usia, jenis kelamin, pendidikan, sosial ekonomi, kebiasaan merokok, konsumsi kopi, kepatuhan diet rendah garam dan aktivitas fisik terhadap pasien hipertensi di Puskesmas Gunung Jati Cirebon. Penelitian ini menggunakan observasional deskriptif, yang dilakukan di Puskesmas Gunung Jati pada bulan Mei-Juni 2025. Besar sampel 65 responden. Dengan total sampling melalui data primer yaitu dengan kuesioner. Analisis data menggunakan univariat. Hasil menggunakan univariat usia (49,2%), jenis kelamin (83,1%) , pendidikan (58,5%), sosial ekonomi (96,9%) , kebiasaan merokok (90,8%), konsumsi kopi (66,2%), kepatuhan diet rendah garam (93,8%) dan aktivitas fisik (69,2%). Penelitian ini terdapat gambaran karakteristik dari usia, jenis kelamin, pendidikan, sosial ekonomi, kebiasaan merokok, konsumsi kopi, kepatuhan diet rendah garam dan aktivitas fisik terhadap pasien hipertensi. Kata Kunci: Hipertensi, Kepatuhan Diet Rendah Garam, Aktivitas Fisik.